Analysis Of The Marketing Strategy of Hajj Financing Products (Prohajj) at PT. Bank Muamalat Indonesia KCU Medan City Hall - Nst, M. Ziqhri Anhar; Marliyah, Marliyah; Nurlaili, Nurlaili (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study was to analyze the marketing strategy for Hajj financing products (prohajj) at PT. Bank Muamalat Indonesia KCU Medan City Hall. This research uses a descriptive qualitative research type. The result of this research is the marketing strategy of PT. Bank Muamalat Indonesia KC Medan Balaikota is quite good, as seen from the product strategy, price strategy, promotion strategy, location strategy, human resources, physical facilities, and processes that have been implemented properly. The existence of internal and external factors in the SWOT analysis has been considered to provide the best service to the community in Hajj financing (Prohajj). Therefore, the marketing strategy for Hajj financing products (prohajj) at PT. Bank Muamalat Indonesia KCU Medan Balaikota has been implemented and provides convenience in service to the community.